Education in the era of IR5.0: are we ready? / Nurul Husna Mahadzir - Mahadzir, Nurul Husna (Universiti Teknologi MARA, Kedah, 2024)
IR 5.0 refers to the collaboration of advanced technologies, such as the Internet of Things (IoT), robotics, and artificial intelligence (AI), with humans to improve efficiency and performance. IR5.0 represents an innovative framework where technology and human capabilities are not in competition but rather in collaboration, intending to achieve higher levels of efficiency, performance, and innovation across various industries.